Combined Effect of Phage phT4A and Pressure-Based Strategies in the Inhibition of Escherichia coli - Carla Pereira; João F. Marques; Sílvia Reis; Pedro Costa; Ana P. Martins; Carlos A. Pinto; Jorge A. Saraiva; Adelaide Almeida (MDPI AG, 2022)
The major concern regarding the bacteriophage (or phage) therapy approach is the regrowth of bacteria after treatment, a consequence of the emergence of phage-resistant mutants. However, this limitation can be overcome by combining different therapies. In this study, the potential of combining phage phT4A with pressure storage (HS) to enhance the control of Escherichia coli and bacterial regrowth after treatment was evaluated. For that, the combining effect of phage phT4A and HS was studied and compared with storage at atmospheric pressure (AP) under refrigeration (4 °C, RF) and room temperature (RT). Initially, the effect of high hydrostatic pressure (200, 300 and 400 MPa) and HS (75 MPa), as well as refrigeration in phage phT4A viability, was determined. However, a considerable phage inactivation was verified at 200 MPa and so only HS at 75 MPa was further studied for combined treatment. The combined treatment with phage phT4A and HS was more efficient (reduction of 2.5 log CFU/mL after 7 days of storage) than phage phT4A (E. coli concentration was similar to that of the bacterial control after 7 days of storage) and HS (reduction of 1.8 log CFU/mL after 7 days of storage) applied individually. The combination of phage phT4A with refrigerated storage did not decrease E. coli levels. However, both the combination of phage with HS and the treatment with HS at 75 MPa effectively reduced E. coli concentration and prevented its regrowth. Phage phT4A viability was slightly affected during HS; however, the efficiency of the combined treatment phage-HS was not compromised. Further studies are needed to validate these findings in food products.